The Impact of Local Government Intervention on The Independence of Village Government Based on the Principle of Subsidiarity in North Bolaang Mongondow Regency - Gobel, Abdul Safar Van; Darmawati, Darmawati; Makkulawuzar, Kingdom (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Local Government intervention in village independence is a crucial problem in the implementation of the principle of subsidiarity in Indonesia. Although Law Number 6 of 2014 concerning Villages recognizes the attributive authority of villages and mandates respect for village autonomy, in practice there are still excessive interventions that hinder the independence of village government. In North Bolaang Mongondow Regency, especially Kaidipang District, local government intervention in villages includes various aspects ranging from development planning, financial management, to setting program priorities that tend to follow district directions. The type of research used is empirical legal research (socio-legal research) with a juridical-sociological approach that is descriptive and analytical. Data sources include primary data obtained through in-depth interviews, participatory observations, and documentation, as well as secondary data in the form of primary, secondary, and tertiary legal materials. The results of the study show that the intervention of the Regional Government of North Bolaang Mongondow Regency has an ambivalent impact, with a more dominant negative impact in the form of reduced community participation in development planning, decreased village flexibility due to strict bureaucratic procedures, inhibition of innovation in the development of local potential, and weakening of participatory democracy. The interventions carried out are not in line with the principle of subsidiarity because there is a reduction in the attributive authority of the village through the restriction of the right of origin and the narrowing of local authority at the village scale. Evaluation based on the four main principles of the principle of subsidiarity shows that the intervention does not meet the presumption in favor of the lower level, adequacy test, necessity test, and proportionality test because the intensity of the intervention exceeds the necessary limit and is disproportionate